Respuesta :
Answer:
[tex]\Huge \boxed{3}[/tex]
Step-by-step explanation:
The function is given :
f(x) = 4x + 15
For f(-3), the input for the function f(x) is -3.
Replace the x variable with -3.
f(-3) = 4(-3) + 15
Evaluate.
f(-3) = -12 + 15
f(-3) = 3
The output for f(-3) is 3.
Answer: f(-3) = 3
Step-by-step explanation: Notice that f is a function of x.
So we want to find f(-3).
We find f(-3) by plugging -3 in for x,
everywhere that x appears in the function.
So we have 4(-3) + 15.
4(-3) is -12 so we have -12 + 15 which is 3.
So f(-3) is 3.